Plzzz Solve

Asked by  | 3rd Oct, 2008, 08:09: PM

Expert Answer:

In right triangle ACE, we have

AC2 + CE2 = AE2                    (1)

In right triangle DCB, we have

DC2 + CB2 = DB2                  (2)

In right triangle ABC, we have

AC2 + CB2 = AB2                  (3)

From (1) and (2), we have

AE+ DB2 = AC2 + CE2 + DC2 + CB2

                   = AB2 + CE2 + DC2           ( from (3))

                  = AB2 + DE2                    (by using the pythagoras theorem in right triangle DCE)

Thus, AE+ DB2 = AB2 + DE2 

Hence proved.

Answered by  | 9th Oct, 2008, 12:13: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.